2020
DOI: 10.1002/admi.202000310
|View full text |Cite
|
Sign up to set email alerts
|

Pt0.25Ru0.75/N‐C as Highly Active and Durable Electrocatalysts toward Alkaline Hydrogen Oxidation Reaction

Abstract: A series of uniform 3.0–3.8 nm Pt1−xRux particles supported on nitrogen‐doped carbon (N‐C) is synthesized by wet‐impregnation, high‐temperature reduction, and high‐temperature NH3 etching. As far as it is known, the resultant Pt0.25Ru0.75/N‐C exhibits the highest activity toward alkaline hydrogen oxidation reaction (HOR) in terms of mass specific exchange current density (j0,m, 1654 A gPtRu−1), that is 4.7 and 1.4 times of commercial Pt/C (352 A gPt−1) and PtRu/C (1213 A gPtRu−1), respectively. The remarkable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The Ru-segregated PtRu demonstrated the highest activity, superior to other Pt and PtRu alloy counterparts (Figure b), which was ascribed to the surface oxophilicity and weaker HBE (reflected by the lower H UPD peak potential, Figure c). A similar Pt 0.25 Ru 0.75 /N–C catalyst with Ru clusters segregated on the surface was reported by Cong et al . In the same vein, the enhancement of HOR activity was also observed in Ru/Pd 3 Ru by Qin et al .…”
Section: Bifunctional Theorysupporting
confidence: 83%
See 1 more Smart Citation
“…The Ru-segregated PtRu demonstrated the highest activity, superior to other Pt and PtRu alloy counterparts (Figure b), which was ascribed to the surface oxophilicity and weaker HBE (reflected by the lower H UPD peak potential, Figure c). A similar Pt 0.25 Ru 0.75 /N–C catalyst with Ru clusters segregated on the surface was reported by Cong et al . In the same vein, the enhancement of HOR activity was also observed in Ru/Pd 3 Ru by Qin et al .…”
Section: Bifunctional Theorysupporting
confidence: 83%
“…Cong et al . investigated the synergistic effect of hydrogen affinity and oxophilicity on the HOR activity in PtRu alloys through CV and CO stripping tests . Thereafter, in the experiment conducted by Alia et al ., a 5% Cu monolayer on the Pt electrode was proved to significantly enhance the HOR activity .…”
Section: Bifunctional Theorymentioning
confidence: 99%
“…Song et al also reported a Pt 0.25 Ru 0.75 /N-C alloy comprising Pt-Ru alloy and surface segregated Ru clusters exhibited excellent mass-specific HOR activity, superior to commercial Pt/C and Pt-Ru/C counterparts. [74] The surface Ru, probably resulting from the annealing process in Ar, endowed Pt 0.25 Ru 0.75 /N-C with appropriate oxophilicity. Notably, the incorporation of Ru also weakened the HBE of Pt due to the electron transfer from Pt to Ru.…”
Section: Synergistic Metal Alloys For Hydrogen Oxidation Reactionmentioning
confidence: 99%
“…Then Ru@Pt core-shell catalysts were synthesized on glassy carbon by UPD-GD approach ( Xing et al, 2020 ). Cong et al synthesized a series of uniform 3.0–3.8 nm Pt1−xRux particles supported on nitrogen-doped carbon (N-C) by wet-impregnation, high-temperature reduction, and high-temperature NH3 etching ( Cong et al, 2020 ). However, the aforementioned catalysts have complex structure and preparation process, and the use of strong reducing agents such as NaBH4 will cause harm to human health.…”
Section: Introductionmentioning
confidence: 99%